Precompensating for spread of excitation in a cochlear implant coding strategy - Bolner, Federico; Magits, Sara; van Dijk, Bas; Wouters, Jan (Hearing research, 2020)
Cochlear implant users’ limited ability to understand speech in noisy environments has been linked to the poor spatial resolution and the high degree of spectral smearing associated with the spread of neural excitation. A sound coding algorithm that aims to improve the spectro-temporal representation of the sound signal at the implanted ear by precompensating the electrical stimulation for the spread of excitation is presented in this study. The spread precompensation algorithm was integrated into the standard clinical advanced combination encoder (ACE) strategy and the resulting strategy was called SPACE. SPACE was evaluated acutely with a group of six implant users and was compared to their daily used ACE strategy in terms of preference rating and speech recognition in four-talker babble and stationary speech-shaped noise. While no significant differences in preference rating were observed, speech recognition in four-talker babble was improved by SPACE processing. Analysis of the group results revealed a significant improvement in mean speech reception threshold (SRT) over the ACE strategy of 1.4 dB in four-talker babble, whereas the difference of 0.9 dB in stationary noise did not reach statistical significance. Assessment of individual differences showed that four out of six listeners obtained significant SRT improvements with SPACE and that no subject scored significantly worse compared to ACE. The results suggest that the proposed sound coding strategy has the potential to improve speech perception for cochlear implant users in challenging listening situations. •A cochlear implant strategy to precompensate stimulation for spread of excitation.•Channel selection and current level are adjusted according to the modelled spread.•Strategy significantly improves speech perception in stationary and babble noise.